On the range of validity of the dipole picture - Ewerz, Carlo; Manteuffel, Andreas von; Nachtmann, Otto (Physical review. D, Particles, fields, gravitation, and cosmology, 2008)
We derive correlated bounds on ratios of deep inelastic structure functions from the dipole picture of photon-hadron scattering at high energies. In particular we consider ratios of the longitudinal structure function, the total structure function, and the charm part of the latter. We also consider ratios of total structure functions taken at the same energy but at three different photon virtualities. It is shown that by confronting these bounds with experimental data we can significantly constrain the range of validity of the dipole picture.
Gesehen am 22.11.2017